2017
DOI: 10.3389/fnana.2017.00106
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stable Value Coding Areas in Caudate Head and Tail Receive Anatomically Distinct Cortical and Subcortical Inputs

Abstract: Anatomically distinct areas within the basal ganglia encode flexible- and stable-value memories for visual objects (Hikosaka et al., 2014), but an important question remains: do they receive inputs from the same or different brain areas or neurons? To answer this question, we first located flexible and stable value-coding areas in the caudate head (CDh) and caudate tail (CDt) of two rhesus macaque monkeys, and then injected different retrograde tracers into these areas of each monkey. We found that CDh and CDt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 103 publications
8
74
0
Order By: Relevance
“…Neurons in cvPut also show similar visual responses (Caan et al., ). These visual responses may be explained by anatomical studies showing that the inferior temporal cortex projects to CDt and cvPut in primates (Griggs et al., ; Kemp & Powell, ; Saintcyr, Ungerleider, & Desimone, ; Yeterian & Vanhoesen, ). Due to the selective projections from CDt and cvPut, neurons in both cdlSNr and cvGPe respond to visual objects, but less selectively (Kim et al., ; Yasuda et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons in cvPut also show similar visual responses (Caan et al., ). These visual responses may be explained by anatomical studies showing that the inferior temporal cortex projects to CDt and cvPut in primates (Griggs et al., ; Kemp & Powell, ; Saintcyr, Ungerleider, & Desimone, ; Yeterian & Vanhoesen, ). Due to the selective projections from CDt and cvPut, neurons in both cdlSNr and cvGPe respond to visual objects, but less selectively (Kim et al., ; Yasuda et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In experiment 1, histology sections of an adult male rhesus monkey ( Macaca mulatta , monkey SM used in the previous studies (Kim & Hikosaka, ; Kim, Ghazizadeh, & Hikosaka, ; Griggs et al., )) was used for immunohistochemistry experiment. In experiment 2, two adult male rhesus monkeys ( Macaca mulatta , monkeys AX and CR) were used for behavioral tasks, neuronal recording, tracer injection and anatomical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, CDh and CDt receive inputs from mostly different areas (e.g., frontal cortex to CDh, temporal cortex to CDt; Yeterian & Van Hoesen, 1978). Even when one area projects to both CDh and CDt, each neuron projects to either CDh or CDt (Griggs et al, 2017).…”
Section: Caudate Tail Circuitmentioning
confidence: 99%
“…Supporting the role of the dorsal striatum as the actor, a number of empirical studies have implicated it in the process of action selection . The dorsal striatum is anatomically divided into dorsomedial and dorsolateral subdivisions (corresponding to the caudate and putamen in primates, respectively); the dorsomedial striatum has been assumed to hold working memory that monitors recent actions to anticipate outcomes and reevaluate the action‐contingent outcomes to select appropriate goal‐directed actions in the future; on the other hand, the dorsolateral striatum has been associated with the transition of behavior to habitual decisions that are insensitive to outcome devaluation.…”
Section: Choice Impulsivity and Dorsal Striatummentioning
confidence: 99%
“…A ventral‐to‐dorsal gradient can be anatomically mapped onto the dorsal striatum based on the afferents from various cortical and subcortical regions . Interestingly, accumulated pieces of evidence from human neuroimaging research have indicated that choice impulsivity could be modulated by such a gradient, but in a distinct anatomical organization (Fig.…”
Section: Evidence From Human Neuroimaging Studiesmentioning
confidence: 99%